New species of Calamoncosis Enderlein (Diptera: Chloropidae) from South Africa - Wheeler, Terry A.; Solecki, Anna M. (Zootaxa, 2013)
Three new and atypical species of Afrotropical Calamoncosis are described: Calamoncosis agricola sp. n. (type locality—South Africa: 15 km E Klaserie); Calamoncosis flavida sp. n. (type locality—South Africa: Roodewal); and Calamoncosis unicornis sp. n. (type locality—South Africa: 15 km E Klaserie). Calamoncosis unicornis exhibits extreme modification and sexual dimorphism in the antenna; in males the arista is reduced to a minute stub and the first flagellomere is greatly elongate and long setulose; in females the arista is well-developed and the first flagellomere is somewhat elongate and pubescent. Calamoncosis agricola is unusual for the genus in that crossvein dm-cu is absent, and C. flavida has an enlarged, rounded first flagellomere. The combination of characters seen in these species expands the known range of morphological variation, and thus the generic limits, of Calamoncosis. Recognition of these new species more than doubles the known Afrotropical fauna of Calamoncosis, previously represented only by C. aenescens (Becker) and C. pauliani (Séguy).